Bridging text and reality: The principles of Tadabbur from An-Nabulsi's perspective in modern tafsir studies - Ridwan, Ali; Zulaiha, Eni (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
This study deeply examines the principles of Tadabbur (contemplation) of Surat Al-Baqarah in Muhammad Ratib An-Nabulsi's exegesis, "Tadabbur Āyātillāh fī al-Nafsi wa al-Kawni wa al-Ḥayāti," and its relevance to contemporary Qur'anic interpretative studies. Tadabbur is essential for holistic Qur'anic comprehension, yet systematic literature on its principles remains limited, especially approaches integrating spiritual, cosmological, and practical life aspects. An-Nabulsi offers a unique methodology bridging sacred texts with modern realities. Employing a qualitative-analytical approach, this study explores An-Nabulsi's Tadabbur principles, highlighting how his exegesis provides a transformative framework for applicable Qur'anic understanding. Findings indicate that An-Nabulsi's principles are highly relevant, offering a new lens for addressing modern human challenges, while enriching the scholarly treasury of tafsir, rendering the Qur'an a dynamic life guide. This research contributes to the development of comprehensive Qur'anic Tadabbur methodologies.